Evaluation of variability in rutting resistance of fine asphalt mixtures (FAM) with 100% RAP (2017)
"The use of RAP (Reclaimed Asphalt Pavement) in hot mix asphalt materials has become a common practice in several countries. Less environmental impact, economic savings and improved mechanical performance are some of the benefits that bring the use of this recycled material. In order to properly reutilize asphalt material on roads, however, it is necessary to study and to analyze the main properties that affect pavement performance. Thus, it is crucial to develop studies to comprehensively characterize the material and predict its behavior on the field. This document presents the results of a project developed under a M.Sc. thesis in Civil Engineering at Universidad de los Andes, which studied the variability on RAP properties from six different sources in the city of Bogotá. RAP characterization included particle size distribution and asphalt percentage. In addition, basic and rheological properties of the recovered RAP asphalt material were also determined. Fine aggregate matrix (FAM) mixtures with 100% RAP were fabricated, in order to determine the mechanical properties of the RAP mixtures and the rutting resistance. For the first time a modified MSCR test was adapted to study the rutting resistance of RAP-FAM materials. The results of the test were satisfactory due the high % of recovery in each RAP sample. The variability of RAP samples was low for the percentage of recovery (COV from 2 to 4%) but higher for the nonrecovery creep parameter (COV of 60%). There is no relation between this COV of the two parameters because the % of recovery is only a percentage, not a measure. Given the high variability for Jnr it is implied that the source of RAP chance the rutting resistance. It is important to control the different sources of the RAP material in order to reduce the high variability."--Tomado del Formato de Documento de Grado.